Red Cell Antibodies Against High Frequency Antigens, A Two Year Experience At A Regional Transfusion Institute - Khurshid, Ayesha; Alam, Maqbool; Mahmood, Asad; Khan, Aysha; Khan, Nabeela; Yazdani, Sajid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the clinicohaematological presentation and outcome of patients with antibodies to high frequency antigen(HFA) in our setup.Study Design: Cross sectional study.Place and Duration of Study: Armed Forces Institute of Transfusion, Rawalpindi, from Jan 2016 to Jan 2018.Methodology: We diagnosed 29 cases of uncommon red cell antibodies including antibodies to HFA, in a span of two years (2016-2018). Information regarding patient’s age, diagnosis, transfusion history, incompatible cross match and history of pregnancy was obtained. Venous blood sample of 3ml was taken in EDTA for grouping, red cell phenotyping and Direct AntiGlobulin Test (DAT) and 5 ml venous blood was taken for Indirect Antiglobulin Test (IAT), antibody screening and identification. Tube method was used for forward and reverse blood grouping, DAT and IAT. Column Agglutination Technique (CAT) was used for antibody screening, identification and red cell phenotyping.Results: Out of a total of 29 cases, 24 (83%) were of anti H antibody (Bombay blood group). Rest of 5 (17%) included one each of anti Rh 17, anti Rh 29 (Rh null), anti P1Pk, anti-ENA/WRB and anti P antibodies. Anti H Lectin (Ulexeuropaeus) was used for confirmation of H antigen absence, while rest of antibodies were confirmed by IBGRL Bristol, UK.Conclusion: The sources of antigen negative blood are family members, rare donor registry, autologous donations and frozen blood banks. Finding compatible blood for patients with an antibody to HFA may be a challenge.